DETERMINAN KEJADIAN DIARE DI DESA SAMURA KECAMATAN KABANJAHE KABUPATEN KARO - Risnawati Tanjung; Rumani Samosir; Nelson Tanjung; Jernita Sinaga; Deli Syaputri (Poltekkes Kemenkes Medan, 2023)
Diarrhea is a disease in which the frequency of bowel movements is more frequent than usual or more than 3 times a day, accompanied by a change in the structure of the stool, which becomes softer and even more liquid. The cause of diarrhea is one of the environmental-based diseases which is still a public health problem where one of the causes of diarrhea is poor environmental sanitation conditions. This study aims to determine the determinants of the incidence of diarrhea in Samura Village, Kabanjahe District, Karo Regency in 2022. This type of research is analytic observation with a cross sectional approach. The population in this study were all heads of families who lived in Samura Village, Kabanjahe District, Karo Regency, totaling 3,398 families, with a sample size of 97 samples. The sampling technique was carried out by means of Simple Random Sampling. Data analysis used the Chi Square test. Based on the results of the study, it can be concluded that there are two variables related to the incidence of diarrhea, namely: personal hygiene with a p-value = 0.014 (p <0.05) and landfills with a p-value = 0.016 (p <0.05) and there are two variables that are not related to the incidence of diarrhea, namely: sources of clean water with a p-value = 346 (p> 0.05) and sewerage with a p-value = 0.472 (p> 0.05). Suggestions for the community to always maintain a clean environment and always apply PHBS, especially in maintaining personal hygiene so that it is far from various diseases